Teachers’ Strategies in Teaching Al-Qur’an Recitation in Sabihisma 4 Kindergarten Padang - Rakimahwati Rakimahwati; Refzi Endah Kurnia Sari; Eka Penti Ernitasari; Asdi Wirman (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aimed to describe the teachers’ strategies in teaching Al-Qur’an recitation to Kindergarten students. This research was a qualitative descriptive research, with the research subject being Sabihisma 4 Kindergarten teachers. Data were collected by observation, interviews, and documentation. The interviews were conducted with six teachers and the principal. The data analysis technique was done by collecting data, reducing data, presenting data and drawing conclusions. While the data validity technique used method triangulation. The results showed that the strategies carried out by the teachers in teaching Al-Qur’an recitations were 1) In planning the teaching, the teachers identified the characteristics of students and designed the lesson plan; 2) In implementation, the teachers used singing methods and question and answer methods. The teachers also used hijaiyah cards and colorful card media to help them teach; and 3) In evaluation, Al-Qur’an recitation examinations were conducted in several steps.